2010
DOI: 10.1111/j.1365-2869.2010.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep duration and all-cause mortality in old age: 9-year follow-up of the Bambuí Cohort Study, Brazil

Abstract: Summary This study investigates the association of sleep duration with risk of all‐cause mortality among elderly Brazilians using data from a 9‐year population‐based cohort study and applying a multivariable longitudinal categorical and continuous analysis using Cox’s proportional hazards models. This analysis used data from the Bambui Health and Ageing Study (BHAS), conducted in Bambuí city (approximately 15 000 inhabitants) in southeastern Brazil. The study population comprised 1512 (86.8%) of all eligible 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 35 publications
(97 reference statements)
4
41
0
1
Order By: Relevance
“…The categories used to analyze the association between sleep duration and health status are based on those used in studies demonstrating associations with mortality risk and the prevalence of illness 41,42,43 . A number of studies,especially those involving elderly individuals, also use the seven to eight-hour sleep duration category as a reference 28,42 , whereas some other studies use the seven-hour category as a reference 25,40 .The present study adopted the seven-hour reference category, leading to similar results.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The categories used to analyze the association between sleep duration and health status are based on those used in studies demonstrating associations with mortality risk and the prevalence of illness 41,42,43 . A number of studies,especially those involving elderly individuals, also use the seven to eight-hour sleep duration category as a reference 28,42 , whereas some other studies use the seven-hour category as a reference 25,40 .The present study adopted the seven-hour reference category, leading to similar results.…”
Section: Resultssupporting
confidence: 66%
“…In the present investigation, however, the analysis was controlled according to the number of chronic diseases, and individuals with physical or mental conditions were rendered incapable of answering the questionnaire and therefore excluded from the study. In a nine-year follow-up study carried out in Brazil, Castro-Costa et al 40 found a strong association between all-cause mortality in the case of long sleep duration patterns but not in the case of short sleep patterns.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
“…** References 11, 21, 23, 25, 26, 27, 29, 32, 33, 34, 36, 39, 40, 41, 44, 46, 47, 48, 49, 51, 52, 53, 54, 56, 57, 61, 64, 66, 68, 70, 71, 72, 77, 79, 80, 84, 86, 87, 88.…”
Section: Notesmentioning
confidence: 99%
“…A frequência de cochilo diurno varia de 22% a 61% dependendo do local do estudo, das características da população estudada e da definição utilizada 28 . Tanto os sintomas de insônia quanto o cochilo diurno são associados à comorbidades e ao maior risco de mortalidade em idosos 24,29,30,31 .…”
Section: Introductionunclassified